Feeding diets with graded levels of fermented soybean meal to Pacific whiteleg shrimp Penaeus vannamei (Boone, 1931): Effect on digestive enzymes, immune responses and carcass composition - Jannathulla, R.; Khan, H. Imran; Thulasi, D.; Kathyayani, S.; Ambasankar, K.; Panigrahi, A.; Muralidhar, M.; Dayal, J. Syama (Indian Journal of Fisheries, 2019)
A 45-days indoor trial was performed to assess the effect of fermented soybean meal (FSBM) on digestive enzyme activity, immune responses and carcass composition of amino acids, fatty acids, and minerals in Penaeus vannamei (Boone, 1931). Five iso-nitrogenous diets were formulated by replacing fishmeal (w/w) with FSBM (200, 250, 300. 350 and 400 g kg-1). A total of 300 juveniles (3.08Â±0.07 g) were randomly distributed to the experimental tanks at the rate of twenty shrimp per tank with three replications for each treatment. Protease activity (p<0.05) decreased with increase in the inclusion level of fermented ingredients. Shrimp fed with FSBM300 diet had a significantly (p<0.05) higher amylase activity than others. Whereas, the lipase activity was not affected significantly due to the dietary change. Total haemocyte count varied from 11.24 to18.54x106 cells ml-1 in FSBM diet fed shrimps. Control group showed highest activity of phenoloxidase (2.85 dopochrome ml-1) but it did not significantly differ from other treatments. Shrimp fed fermented ingredients had no significant difference in carcass amino acids. Eicosapentaenoic (C20:5) and docosahexaenoic acids (C22:6) were significantly (p<0.05) affected in shrimp reared with FSBM350 and FSBM400 diets. Calcium had a significant difference between the treatments, while other elements were not influenced. The results concluded that fishmeal could be partially substituted with fermented ingredients in the diet of P. vannamei without having any negative effect on immune responses and carcass micro-nutrients. Keywords: Carcass composition, Digestive enzyme, Fermented ingredient, Immune response, Penaeus vannamei, Soybean meal